The Determinants of Millennial Stock Market Participation: Empirical Testing of Theory of Planned Behavior - Eka Bertuah; Jong Sandy (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. This study aims to determine the effects of financial literacy, financial well-being, overconfidence bias, risk tolerance, herding behavior, and social interaction on investment intention, as well as the role of investment intention as a moderating variable that relates these variables to the participation of millennial employees in the stock market during the COVID-19 pandemic. The target population of this research is millennial employees who have participated in the stock market. For sampling, this study uses the purposive sampling method. The data analysis technique used is the structural equation method. The results of this study are that financial literacy, financial well-being, risk tolerance, and social interaction are proven to positively influence investment intention. Furthermore, investment intention has a positive effect on stock market participation. Furthermore, investment intention cannot mediate the relationship between financial literacy, financial well-being, overconfidence bias, risk tolerance, herding behavior, and social interaction on stock market participation. Overconfidence bias and herding behavior do not have a positive effect on investment intention. This study proves that financial literacy, financial well-being, risk tolerance, and social interaction among millennial employee investors can encourage their intention to invest. However, the uncertainty of investment returns during the COVID-19 pandemic mitigated the investment intention of these millennials and did not encourage them to participate in the stock market. Thus, the research provides empirical evidence on the Theory of Planned Behavior for millennial employee investors in encouraging their intention to invest in the stock market.Keywords: Financial literacy, financial well-being, risk tolerance, social interaction, and investment intentions.Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh literasi keuangan, kesejahteraan keuangan, bias terlalu percaya diri, toleransi risiko, perilaku menggiring, dan interaksi sosial terhadap niat investasi, dan peran niat investasi sebagai variabel moderasi yang menghubungkan variabel-variabel tersebut dengan partisipasi karyawan milenial pada pasar saham selama pandemi Covid 19. Populasi dalam penelitian ini adalah pegawai milenial yang berinvestasi saham di pasar modal. Teknik pengambilan sampel menggunakan metode purposive sampling. Teknik analisis data menggunakan Metode Persamaan Struktural. Hasil penelitian membuktikan bahwa literasi keuangan, kesejahteraan keuangan, toleransi risiko, dan interaksi sosial dapat mempengaruhi niat investasi secara positif. Selanjutnya niat investasi berpengaruh positif terhadap partisipasi pasar saham. Selanjutnya, niat investasi tidak dapat memediasi hubungan antara literasikeuangan, kesejahteraan keuangan, bias terlalu percaya diri, toleransi risiko, perilaku menggiring, dan interaksi sosial terhadap partisipasi pasar saham. Bias terlalu percaya diri dan perilaku menggiring tidak berpengaruh positif terhadap niat investasi. Penelitian ini memberikan bukti bahwa literasi keuangan, kesejahteraan keuangan, toleransi risiko, perilaku menggiring dapat mendorong niat karyawan milenial untuk berinvestasi. Akan tetapi kondisi ketidakpastian ketika mereka berinvestasi selama pandemi Covid 19 tidak mendorong niat mereka untuk berpartisipasi dalam pasar saham. Dengan demikian penelitian ini memberikan bukti empiris atas Teori Perilaku yang Direncanakan pada karyawan milenial dalam mendorong niat mereka berinvestasi di pasar saham.Kata kunci:Literasi keuangan, kesejahteraan keuangan, toleransi risiko, interaksi sosial, dan niat investasi.